Alteration of chemical attributes of a yellow oxisol by surface liming in area under mango crop - Araújo, Fernando Silva; Salviano, Adeodato Ari Cavalcante; Coelho Filho, Aluizio Duarte (Semina: Ciências Agrárias, 2009)
This study was developed to evaluate the effect of different limestone rates on the soil acidity and Ca2+ and Mg2+ contents in different depths, when the limestone was applied in to surface of the soil, in an area already implanted with the mango crop. The experiment was accomplished in the experimental field of Soinho's Agricultural Family School, in Teresina, PI. The experimental design was completely randomized with four treatments based in the limestone levels: 0; 0.5; 1.0 and 2.0 Mg ha-1, and four replications totalizing 16 plots, with 80 m2 each. The samplings were accomplished at four, eight and sixteen months after the application of the limestone. In each plot four simple samples were collected to form one bulked sample in the depths (0.00 - 0.05; 0.05 - 0.10; 0.10 - 0.15 and 0.15 - 0.20 m). The results were submitted to the variance and regressions analysis, according to the procedure of the SAS software. The effect of the limestone application in the soil surface on pH, Al3+, H+ , Al3+ and Mg+2 contents were intensified in function of the time.